Study of Physio-Chemical Properties of Local Potato Cultivars Grown in Different Districts of Gandaki Province (Nepalese Horticulture, 2025)
A study was conducted in 2024 across six districts of Gandaki Province to identify and evaluate the physio-chemical properties of different potato varieties. The objectives included mapping production areas, analyzing physical and chemical properties, and determining processing suitability via sensory evaluation. The physical traits assessed included tuber shape, weight, size, eye depth, flesh and skin color, and skin texture. Specific gravity, starch content, reducing sugar content, and dry matter content were the chemical parameters analyzed. This study revealed significant variations among the tested varieties. Tuber shapes ranged from oval to round, weighing 23.00 to 125.33 grams. Flesh colors varied from white to creamy white, and skin colors included white, purple, and red. All samples tested had smooth skin surfaces. Biochemical analysis revealed a reducing sugar concentration from 103.77 to 345.81 mg/100 ml, a dry matter content ranging from 12.40% to 29.94%, and a specific gravity between 1.08 and 1.11. The starch content ranged from 3.10% to 6.13%. Tharu Local, Mustang White Large, and Lahachok were found to be most suitable for chips and fries due to their high dry matter and starch content. Hemja and Jhakala were the most preferred in the organoleptic tests. This study suggests genetic profiling and legal registration of these varieties from the concerned authorities for preserving and improving the local potato cultivation.